(untitled) (Boston, 2009)
Women’s Voices is an introductory women's studies reader crafted to include a balance of recent contemporary readings with historical and classic pieces. This student-friendly text provides short, accessible readings reflecting the diversity of women’s experiences. Chapter introductions provide background information on each chapter's topic, including explanations of key concepts and ideas and references to the subsequent reading selections. This new edition includes revised chapter framework essays that reflect the most up-to-date research and theory in the field
Keywords: Women’s studies,Feminism,Chủ nghĩa nữ quyền,Ngành phụ nữ học